Citizen monitoring of invasive species: wing morphometry as a tool for detection of alien Tetropium species. (25th October 2016) - Goczał, J.; Rossa, R.; Sweeney, J.; Tofilski, A.
Abstract: The increasing threat of alien wood‐boring insect has resulted in the initiation of large‐scale monitoring programmes. These programmes are most often based on pheromone‐bailed traps, which allow the early detection and monitoring of invasive species. This approach is expensive because it entails the processing and accurate identification of large numbers of specimens. One of the most often suggested solutions to this problem is citizen participation in the monitoring of invasive species. Such an approach has the potential for reducing costs as well as providing data from a larger number of sites. However, citizens vary in taxonomic expertise and experience which can result in identification errors. This may be particularly important in the case of wood borers which include many morphologically similar species. In this study, we develop and discuss a semi‐automated method of identifying four morphologically similar and invasive Tetropium spp. wood borers as a potential tool for citizen‐based monitoring programmes. Identification is based on wing measurements and requires neither specialist knowledge nor expensive equipment. The method correctly identified the species of Tetropium with an error ranging from 1.3% for T. fuscum to 7.5% for T. cinnamopterum . We found that experience level of the individual user was not essential for correct identification; on average, inexperienced volunteers correctly identified the Tetropium species in 93% of cases. Further development of this method may be a significant step to overcoming the taxonomical impediment to citizen monitoring of taxonomically challenging groups of insects.